2020
DOI: 10.1177/0193945920980743
|View full text |Cite
|
Sign up to set email alerts
|

Review of Mental Health First Aid Programs

Abstract: Mental health first aid programs are interventions to empower the community to help people with mental health problems/crises. A review of these programs was conducted in accordance with the guidelines of the Joanna Briggs Institute. Published and unpublished works from 2009 to 2019 were considered. The review included 252 studies. Several Mental Health First Aid programs were identified, with varying characteristics, participants, and contexts of implementation. These group interventions were carried out amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…They also mentioned that mental health problems should be taught. The problems described were cognitive, emotional, behavioural and relational, as in Costa et al (2020) review. These authors refer to Mental Health Training Programmes addressing mainly pathologies (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They also mentioned that mental health problems should be taught. The problems described were cognitive, emotional, behavioural and relational, as in Costa et al (2020) review. These authors refer to Mental Health Training Programmes addressing mainly pathologies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These authors mapped these interventions, identifying their characteristics, participants and implementation contexts. One of the findings indicated that Mental Health First Aid Training Programmes seem suitable for adolescents in upper secondary schools (Costa et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations